Extracellular matrix dynamics in cell migration, invasion and tissue morphogenesis - Yamada, Kenneth M. (Int J Exp Pathol, 2019)
This review describes how direct visualization of the dynamic interactions of cells with different extracellular matrix microenvironments can provide novel insights into complex biological processes. Recent studies have moved characterization of cell migration and invasion from classical 2D culture systems into 1D and 3D model systems, revealing multiple differences in mechanisms of cell adhesion, migration and signalling—even though cells in 3D can still display prominent focal adhesions. Myosin II restrains cell migration speed in 2D culture but is often essential for effective 3D migration. 3D cell migration modes can switch between lamellipodial, lobopodial and/or amoeboid depending on the local matrix environment. For example, “nuclear piston” migration can be switched off by local proteolysis, and proteolytic invadopodia can be induced by a high density of fibrillar matrix. Particularly, complex remodelling of both extracellular matrix and tissues occurs during morphogenesis. Extracellular matrix supports self‐assembly of embryonic tissues, but it must also be locally actively remodelled. For example, surprisingly focal remodelling of the basement membrane occurs during branching morphogenesis—numerous tiny perforations generated by proteolysis and actomyosin contractility produce a microscopically porous, flexible basement membrane meshwork for tissue expansion. Cells extend highly active blebs or protrusions towards the surrounding mesenchyme through these perforations. Concurrently, the entire basement membrane undergoes translocation in a direction opposite to bud expansion. Underlying this slowly moving 2D basement membrane translocation are highly dynamic individual cell movements. We conclude this review by describing a variety of exciting research opportunities for discovering novel insights into cell‐matrix interactions.